Santa Rosa de Lima and Descartes - Secada, Jorge (2019)
Through a comparison between the roads to the contemplation and love of God of the cartesian meditator and of Saint Rose of Lima, the paper reveals an essential but ignored aspect of Descartes’s Meditations on First Philosophy. This leads the author to the formulation of interesting problems relating to the very nature of philosophy and the relations between knowledge, understanding, and life.